A framework for bridging the gap in the care of familial hypercholesterolaemia in the community: pragmatic and economic perspectives - Purchase, S.; Vickery, A.; Garton-Smith, J.; O'Leary, Peter; Sullivan, D.; Slattery, M.; Playford, D.; Watts, G. (Wiley, 2014)
Objective: To analyze various business models for improving the diagnosis and treatment of familial hypercholesterolaemia.Methods: Five different strategies were analyzed and data were collected through documentary analysis andstructured interviews. Interviewees included professionals from universities, Western Australia Department of Health,private medical practitioners and not-for-profit organizations.Results: Two business models are recommended: alliance with general practitioners and primary health careorganizations and a joint venture model between private cardiology clinics and lipid disorder clinics in the publicsector. Primary care providers are in a good position to co-ordinate across the multi-disciplinary health servicesrequired to treat familial hypercholesterolaemia within the population.Conclusions: Devolution of knowledge on treatment of familial hypercholesterolaemia from centralized specialisthospital clinics to primary care services is required to improve the rate of detection of this condition in the community.An International Classification of Disease (ICD)-10 and/or a Diagnosis-Related Group (DRG) code is required to codify,catalogue and document new cases and treatment, as well as to facilitate research and re-imbursement strategies.Primary Health Care Organizations can usefully facilitate the transfer of knowledge on best standard of care to generalpractice, but the best model of care will require close integration of care with specialist and academic centres.